2019
DOI: 10.1111/ecc.12993
|View full text |Cite
|
Sign up to set email alerts
|

Routine follow-up care after curative treatment of head and neck cancer: A survey of patients’ needs and preferences for healthcare services

Abstract: Objective The experience of a cancer diagnosis and receiving treatment can have profound impacts on health and subsequently patients may require significant support. Often, these needs are not identified or addressed. Given that less is known about the follow‐up requirements for head and neck cancer patients, this study aimed to describe their follow‐up needs and preferences. Methods In Ontario, Canada from 2012–2014, 175 patients completed a questionnaire at an appointment one year after treatment. To identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 33 publications
1
21
0
1
Order By: Relevance
“…Although we agree with the authors that unnecessary follow‐up checks represent an economic burden to the health care system, we would like to point out that (a) HPV‐related OPSCC exhibits a distinct pattern of dissemination occurring after a longer period of time than in HPV‐negative cases etiologically linked to tobacco and alcohol exposure, (b) while locoregional recurrence is the dominant site of failure in patients with HPV‐negative tumors, HPV‐associated OPSCC relapses primarily at distant organs including unusual sites such as skin, brain, skeletal muscles, intra‐abdominal or pericardial lymph nodes, kidney, and pancreatic tail, (c) within the group of HPV‐associated locoregionally advanced OPSCC there are different risk categories, that is, those with HPV‐positive OPSCC tumors with a 3‐year survival expectation of over 90%, but also an HPV‐positive OPSCC with a clearly less favorable outcome (3‐year overall survival around 70%); in particular, patients with HPV‐positive T4 tumors and N3 disease have an inadequate distant disease control, which might even ask for treatment intensification, (d) there is a trend to de‐escalate treatment in HPV‐associated OPSCC, and the outcome of such procedures might be quite disappointing, as we recently have noticed in two randomized trials comparing concurrent cisplatin‐based chemoradiation vs cetuximab/radiation both in low‐ and intermediate‐risk HPV‐positive OPSCC patients, De‐ESCALaTE HPV and RTOG1016, pointing at the fact that such patients still benefit most from the standard treatment approach, cisplatin‐based chemoradiation, and that in particular late side‐effects accompanying this approach might be a threat in such patients, who are usually younger and have a longer life expectancy than HPV‐negative OPSCC patients, and that some of these side effect might occur even after 5 years, (e) posttreatment surveillance takes on further roles involving early psychosocial interventions, appraisal by speech and language therapists, restoration of nutritional, swallowing, and dental status, and detection of endocrine deficiencies, all of which contribute to a holistic approach in cancer management, and (f) in the era of shared medical decision making, patient voice should also be heard and clearly not all patients favor a less intensive follow‐up, especially in terms of imaging methods …”
supporting
confidence: 77%
“…Although we agree with the authors that unnecessary follow‐up checks represent an economic burden to the health care system, we would like to point out that (a) HPV‐related OPSCC exhibits a distinct pattern of dissemination occurring after a longer period of time than in HPV‐negative cases etiologically linked to tobacco and alcohol exposure, (b) while locoregional recurrence is the dominant site of failure in patients with HPV‐negative tumors, HPV‐associated OPSCC relapses primarily at distant organs including unusual sites such as skin, brain, skeletal muscles, intra‐abdominal or pericardial lymph nodes, kidney, and pancreatic tail, (c) within the group of HPV‐associated locoregionally advanced OPSCC there are different risk categories, that is, those with HPV‐positive OPSCC tumors with a 3‐year survival expectation of over 90%, but also an HPV‐positive OPSCC with a clearly less favorable outcome (3‐year overall survival around 70%); in particular, patients with HPV‐positive T4 tumors and N3 disease have an inadequate distant disease control, which might even ask for treatment intensification, (d) there is a trend to de‐escalate treatment in HPV‐associated OPSCC, and the outcome of such procedures might be quite disappointing, as we recently have noticed in two randomized trials comparing concurrent cisplatin‐based chemoradiation vs cetuximab/radiation both in low‐ and intermediate‐risk HPV‐positive OPSCC patients, De‐ESCALaTE HPV and RTOG1016, pointing at the fact that such patients still benefit most from the standard treatment approach, cisplatin‐based chemoradiation, and that in particular late side‐effects accompanying this approach might be a threat in such patients, who are usually younger and have a longer life expectancy than HPV‐negative OPSCC patients, and that some of these side effect might occur even after 5 years, (e) posttreatment surveillance takes on further roles involving early psychosocial interventions, appraisal by speech and language therapists, restoration of nutritional, swallowing, and dental status, and detection of endocrine deficiencies, all of which contribute to a holistic approach in cancer management, and (f) in the era of shared medical decision making, patient voice should also be heard and clearly not all patients favor a less intensive follow‐up, especially in terms of imaging methods …”
supporting
confidence: 77%
“…Whereas the National Comprehensive Cancer Network recommends Cancer February 15, 2020 regular clinical assessments at follow-up, with imaging to be performed if clinically indicated or with routine annual imaging, 12 many institutional and trial protocols require patients to undergo follow-up surveillance imaging at regular intervals. 17 There have been several studies exploring PET imaging as a modality to detect residual HNC after treatment and to predict for future recurrences. 13 There is evidence that frequent surveillance imaging may not affect patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a recent survey of 175 patients with HNC at 1-year posttreatment follow-up in Ontario, Canada, indicated that only 66% of felt that they needed imaging. 17 There have been several studies exploring PET imaging as a modality to detect residual HNC after treatment and to predict for future recurrences. [18][19][20][21][22][23][24][25][26][27] In a metaanalysis comprising of 51 studies, Gupta et al 28 reported that the negative predictive value of a negative posttreatment PET scan is high at 95%.…”
Section: Discussionmentioning
confidence: 99%
“…other medical conditions may require more attention. 29 Regardless, it is important to note that when surveyed, HNC survivors do appear to prefer following up with their oncologists, 30 and even after 5 years, these patients remain focused on surveillance testing for the purpose of detecting recurrences rather than managing long-term sequelae of treatment. 31 Patient survey responses must be carefully interpreted, however, because patients have been demonstrated to have been satisfied with their care when transitioned from a surgeon to a multidisciplinary survivorship clinic.…”
Section: Continuedmentioning
confidence: 99%